A Comparative Legal Analysis of Intellectual Property as Marital Property: Perspectives from Indonesia, the United States, and Europe - Yudika Dwi Erwanda; Darmawan Darmawan; Azhari Azhari (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the regulation of copyright royalties as marital property in Indonesia, the United States, and Europe, aiming to provide recommendations for better legal implementation. It applies a case approach and a comparative law approach, using library research and qualitative analysis. The findings show that Indonesia, the United States, and Europe share similarities in recognizing royalties as marital property. However, European countries tend to more clearly distinguish between exclusive rights and economic rights, while the United States demonstrates considerable flexibility through its regulatory variations. Indonesia still requires clearer and more comprehensive regulations to ensure legal certainty regarding the status of royalties as marital property and their distribution after divorce.